1987
DOI: 10.1128/aem.53.5.1020-1027.1987
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of putrefactive anaerobe 3679 caused by stringent-type response induced by protonophoric activity of sorbic acid

Abstract: The inhibitory effects of potassium sorbate on the bioenergetics, phenylalanine uptake, protein synthesis, and certain aspects of cell regulation were examined in putrefactive anaerobe 3679. Undissociated sorbic acid appeared to act as a protonophore by lowering the intracellular pH and dissipating the proton motive force of the membrane. Sorbate inhibited the uptake of phenylalanine, decreased the rate of protein synthesis, and altered patterns of phosphorylated nucleotide accumulation, resulting in increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Additional toxic effect of acetic acid on cells by modification of physiological and metabolic activities was also demonstrated (Eifert et al 1997;Jensen et al 2003). Even if the mechanism of action of potassium sorbate has remained uncertain, it is partly based on its ability to inhibit the amino acid uptake in Penicillium chrysogenum and in vesicles of some bacteria (Ronning and Hilmer 1987). Our results confirmed that organic acid salts did not have the same inhibitory effect according to their nature.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Additional toxic effect of acetic acid on cells by modification of physiological and metabolic activities was also demonstrated (Eifert et al 1997;Jensen et al 2003). Even if the mechanism of action of potassium sorbate has remained uncertain, it is partly based on its ability to inhibit the amino acid uptake in Penicillium chrysogenum and in vesicles of some bacteria (Ronning and Hilmer 1987). Our results confirmed that organic acid salts did not have the same inhibitory effect according to their nature.…”
Section: Discussionsupporting
confidence: 65%
“…2003). Even if the mechanism of action of potassium sorbate has remained uncertain, it is partly based on its ability to inhibit the amino acid uptake in Penicillium chrysogenum and in vesicles of some bacteria (Ronning and Hilmer 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Disinfectant-induced structural changes in fully developed spores have been described (123,168,189), but these have not been fully related to their biochemical effects on sporulating cells. Thus, the mechanism of action (see later section) of many sporicidal agents is still often poorly described.…”
Section: Sporulationmentioning
confidence: 99%
“…Several antibacterial agents are known to inhibit germination. These include alcohols, aldehydes, phenols and cresols, parabens, sorbic acid, and mercuric chloride (2,3,47,66,68,100,128,148,149,156,166,168,171,172,181,190,193,195,198,219,220,223,234; B. M. Lund, Ph.D. dissertation, University of London, London, England, 1962). This inhibition (Table 10) occurs at concentrations that are closely related to those that inhibit the growth of vegetative bacteria.…”
Section: Germinationmentioning
confidence: 99%
See 1 more Smart Citation